Sedimentological control of gold and uraninite mineralisation in the White Reef of the West Rand - Steyn, L S (My University, 1975)
The primary objective of the study was to determine the controls of mineralization in the White Reef, which occurs at the base of the Bird Reef Stage of the Upper Witwatersrand System on the West Rand. It is a quartzite with scattered pebbles and occasional 'banket' conglomerates. The average gold content at 317 gm-cm per tonne is low, but uranium grade is amongst the highest on the Witwatersrand. In 1963 the author demonstrated some sedimentological properties of the Livingstone Reef are qualitatively related to gold content. More intensive studies have since confirmed the sedimentological control of gold mineralization. For instance, Pretorius (1974 a, 1975) recognizes a general fluvial fan geometry for the Witwatersrand reefs. However other factors, such as variations in environments, mechanisms of deposition, and behavior of the heavy minerals require further clarification; these form the main subject matter of this study. A pilot study established interrelationships between sedimentary features and ore grade. Follow-up work revealed systematic downslope changes. The reef was sampled on a systematic grid over the four West Rand mines. All pebbles were measured over complete reef sections. Measurements include 526 of reef thickness, 1 312 of crossbedding, 45 ripple marks, 2 of sand waves, 63 801 of pebble size and sorting, 63 761 for packing, 1 200 of fabric, 33 987 of composition, and 1 162 of shape and sphericity. Very large numbers of gold and uranium values, reef elevations, and thicknesses were compiled from records. The area investigated formed a subsiding part of a basin edge between granitic buttresses. Primary structures include the north-south Randfontein trough in the west, which controlled sedimentation from the Main Reef Stage onwards and the smaller north-east trending Witpoortjie trough. Additional control was exercised later by northeast and northwest-trending depressions. The major West Rand syncline running north-west, and the basin north of the Witpoortjie fault, are post-depositional features. The White Reef is comparable in geometry and sedimentological features to the Basal Reef (Sims, 1969) and generally conforms to the model of Pretorius (197 5). The subsiding Randfontein trough controlled the direction of major pay shoots, whilst smaller paystreaks formed along braided channels. The paleo-environment for the White Reef was that of a braided fluvial fan conforming to the model of Eynon and Walker (1974) for braided rivers. The distribution of depositional facies is related to fan geometry. (Abbreviations abstract)
A Thesis Submitted for the Degree of Ph.D. in the Faculty of Science, University of the Witwatersrand, Johannesburg.
Keywords: Gold ores -- Geology -- South Africa -- Witwatersrand.; Uranium ores -- Geology -- South Africa -- Witwatersrand.; Mineralogy -- South Africa -- Witwatersrand.; Reefs -- South Africa -- Witwatersrand.